Effect of Nigella sativa Nasal Spray on the Treatment of Chronic Rhinosinusitis Without a Nasal Polyp - Rezaeian, Ahmad (Allergy Rhinol (Providence), 2018)
BACKGROUND: Chronic rhinosinusitis (CRS) is a common inflammatory disease of nasal and paranasal sinuses, with many treatment methods available for the management of this disease. Recently, herbal medicines have shown a significant impact on inflammatory diseases such as CRS, and one of these herbal medicines is Nigella sativa. Therefore, the current study aimed to evaluate the effectiveness of N. sativa in patients with CRS without nasal polyp (CRSsNP). METHODS: In this randomized clinical trial, 65 patients with mild to moderate CRSsNP were enrolled based on the inclusion criteria. Patients were divided randomly into 2 parallel groups: intervention and placebo groups. Patients in the intervention group received 2 puffs/day of N. sativa nasal spray (1 g/day of N. sativa) and in the placebo group received 2 puffs/day of sodium chloride spray 0.65%. RESULTS: Thirty-one patients (19 men and 12 women) in the intervention group and 34 in the placebo group (18 men and 16 women) were evaluated. Lund–McKay, Lund Kennedy, and Sino-Nasal Outcome Test-22 scores were assessed for both groups after 8 weeks of treatments. These scores decreased significantly in both groups. However, these scores were significantly lower in the intervention group compared with the placebo group (P < .0001, for all). CONCLUSION: The use of N. sativa nasal spray has symptom reliever effect with no adverse effects in patients with CRSsNP.